Back to the Pavilion - Attiqur Rahman, M. (Karachi, Pakistan Oxford Unviersity Press, 2005)
Memoirs of the author, a Pakistani military leader.
Include Index and Illustration
Keywords: Pakistan -- Pakistan. Army -- Generals